The world is not enough: New diplomacy and dilemmas for the World Heritage Convention at 50. Issue 4 (29th November 2022) - Meskell, Lynn; Liuzza, Claudia
Abstract: In this article, we reflect on the current socio-political context of the 1972 World Heritage Convention after 50 years rather than its significant achievements and trials throughout its turbulent history. The United Nations Educational, Scientific and Cultural Organization (UNESCO) has already documented and publicized these formative episodes. Instead, we consider the World Heritage milieu today, embedded as it is within a much broader landscape of non-governmental organizations and civil society preservation initiatives than it was five decades ago. Like other United Nations agencies, UNESCO now faces challenges arising from various types of re-spatialization beyond the nation-state that further impact its effectiveness. Those challenges encompass not only the expansive force of globalization but also regionalization and localization, all of which have given rise to a new diplomacy. We discuss the proliferation of competing international agencies and individual donors, then describe the dilemmas facing World Heritage, including the rise of non-state actors and post-conflict remediation in the Middle East, the limited recognition of Indigenous Peoples and their role in decision making, and the persistent failures to remedy the inequitable position of Africa as a priority region.